2015
DOI: 10.1007/s00404-015-3921-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal super-obesity

Abstract: Maternal super-obesity poses a high-risk situation for mother and child which generally demands a higher amount of perinatal care. The number of deliveries by super-obese mothers remained stable over the study period. Primary c-section was the most frequent mode of delivery. Of the parturients who opted for vaginal delivery nearly half of the deliveries had to be completed by secondary c-section. Over-all peripartal maternal complications did not exceed average.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
6
20
1
Order By: Relevance
“…With over 99% complete data on maternal BMI over a six‐year period, our study is the first contemporary Australian study to report on the prevalence and outcomes of severe maternal obesity in a non‐tertiary hospital. Our study confirms that obesity is common among Australian obstetric patients and that increasing BMI is linked to a number of pregnancy and neonatal complications . It also provides point estimates of these complications for the severely obese obstetric patient delivering in a non‐tertiary hospital.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…With over 99% complete data on maternal BMI over a six‐year period, our study is the first contemporary Australian study to report on the prevalence and outcomes of severe maternal obesity in a non‐tertiary hospital. Our study confirms that obesity is common among Australian obstetric patients and that increasing BMI is linked to a number of pregnancy and neonatal complications . It also provides point estimates of these complications for the severely obese obstetric patient delivering in a non‐tertiary hospital.…”
Section: Discussionsupporting
confidence: 78%
“…The prevalence of BMI ≥50 kg/m 2 in this study (0.5%) lies within the range reported elsewhere in international studies, 0.06–2.2% . However, due to methodological differences, care needs to be taken when comparing these results.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Compelling clinical data have demonstrated that maternal obesity closely associates with neonatal hypoglycemia (1)(2)(3)(4)(5)(6)(7). Most importantly, maternal BMI predicts neonatal hypoglycemia independent of maternal glucose concentrations, indicating that maternal obesity itself imposes a major risk for neonatal hypoglycemia (1,8,9).…”
mentioning
confidence: 99%